HUBUNGAN PERILAKU KELUARGA DENGAN RISIKO STUNTING PADA BALITA DI RT 64 RW 17 KELURAHAN 16 ULU KECAMATAN SEBERANG ULU II PALEMBANG - Subhan Muhith; Pitri Lismawati (IKesT Muhammadiyah Palembang, 2024)
ABSTRACT Background: Stunting is a condition where a child experiences growth failure that occurs in the body and brain due to long-term malnutrition which results in the child being shorter than normal children of his age. The latest data also shows that around 9 million Indonesian toddlers are currently stunted. Objective: This study aims to determine the relationship between family behavior and the risk of stunting in toddlers in RT 64, Kelurahan 16 Ulu, Seberang Ulu IIPalembang District in 2023. Methodology: The research method used was an analytical survey with a cross sectional design. The number of samples in the study was 32 respondents. Furthermore, the data that has been collected is processed and analyzed using the Chi-Square statistical test with a significance level (p<0.05). In the results: the Chi-Square statistical test showed that there was a significant relationship between knowledge (p=0.038), attitudes (p=0.034), and actions (p=0.012) with the risk of stunting in RT 64 sub-district 16 Ulu, Seberang Ulu II District. Conclusion: This research shows that family knowledge, attitudes and actions are related to the risk of stunting. It is hoped that future researchers will examine the relationship between family behavior and the incidence of stunting in toddlers with different designs and research methods.